Pengaruh Pemberian Diet Bubur Tempe Terhadap FrekuensiBab Pada Anak Diare Di Ruang Mina Rumah Sakit Pku Muhammadiyah Surakarta - Setiawati, Heni, Endang Zulaicha, S.Kp (2016)
Diarrhea is accompanied by digestive disturbances defecation frequency abnormal (increased) and the more mushy stool consistency or liquid. The use of slurry tempeh seen can help speed healing of diarrhea patients, this is due to soybean is made from basic ingredients contain substances soy, energy, protein, fat, HA, and is rich in fiber, calcium, vitamin B and iron is needed to cure patients of diarrhea. The purpose of this study was to determine the effect of dietary soybean porridge to frequency of defecate of children diarrhea in Room Mina Hospital PKU Muhammadiyah of Surakarta. This is study using a quasi experimental. The population in this study were all patients at room Mina Hospital PKU Muhammadiyah of Surakarta, amounting to 188 children aged 3-5 years in one month. The sample used in this study were as many as 30 people were divided into 2 groups, ie 15 people for a group of patients who were given Soybean porridge (experimental group) and 15 people for a group of patients who were given Preda porridge (control group). The sampling technique was done by accidental sampling. Data collection techniques using observation sheet. Data analysis techniques in this study using univariate and bivariate analysis. Results of analysis of the data showed that: Most of the frequency of defecate before being fed a diet of soybean porridge between 5-10 x /day in the amount of 7 children (46.67%), after being given a diet of soybean porridge majority frequency of defecate diarrhea to 1-4 x /day is equal 14 children (93.33%). The majority of the frequency of defecate before being given a diet of Preda porridge between 5-10 x /day in the amount of 9 children (60%), after being given a diet of porridge Preda there are 6 children (40) the frequency of defecate diarrhea between 1-4 x/day. There are differences in the average frequency of defecate before being fed a diet of porridge or gruel Preda porridge with given diet after Soybean porridge or Preda porridge value = 0.000. There is the effect of dietary soybean porridge to the frequency of defecate diarrhea at children in room Mina Hospital PKU Muhammadiyah of Surakarta.